1850 Mass. Acts 401, § 2 - (:unkn) unknown (My University, 1850)
Ch. 194, § 2: Prohibited the manufacture or sale of slung-shots. Violators fined not less than fifty dollars or imprisoned not exceeding six months.
Keywords: TRANSFER, MANUFACTURE & POSSESSION - NON-GUN ARMS